Peningkatan Sikap Positif dan kemampuan Berpikir Kreatif Siswa dengan Pendekatan RME pada Materi Aritmatika Sosial di Kelas VII SMP Swasta Trisakti Pematangsiantar - Agus Junsion Naibaho (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2019)
Mathematics is an important lesson, especially because mathematics can be used in everyday life to solve problems. But this is not the case when met in the field, one of the 'popular' subjects as a less desirable subject is mathematics. Furthermore, creative thinking is the ability to make new combinations, based on data, information or elements that exist. The objectives in this study were: To determine the improvement of creative thinking skills and positive attitudes of students by using the realistic mathematical education (RME) approach in learning mathematics at the Trisakti Private Middle School Pematangsiantar T.A. 2018/2019. This research is a quasi-experimental study. The population in this study were all seventh-grade students of Pematangsiantar Trisakti Private Middle School, which consisted of 3 parallel classes with an average number of students per class of 30 people. From 3 class VII parallel, students were selected as a sample of 1 class to be used as Experimental class, namely Class VII-A. Hypothesis testing uses Paired-Samples t-Test with a significance level of 0.05. Test criteria if Î±> Sig. (2-tailed) then reject Ho and Ha accepted. The results showed that there was a significant increase in positive attitudes with RME in social arithmetic material in class VII of Pematangsiantar Trisakti Private Middle School, there was a significant increase in the ability to think creatively with the RME approach to social arithmetic material in class VII Pematangsiantar Trisakti Private Middle School. Keywords : Positive Attitudes, Creative Thinking Skills, Realistic Mathematical Education